Mesenchymal Stem Cells as Therapeutic Agents and Novel Carriers for the Delivery of Candidate Genes in Acute Kidney Injury - Yuxiang Liu; Jingai Fang (Hindawi Limited, 2020)
Acute kidney injury (AKI) is a heterogeneous syndrome characterized by a dramatic increase in serum creatinine. Mild AKI may merely be confined to kidney damage and resolve within days; however, severe AKI commonly involves extrarenal organ dysfunction and is associated with high mortality. There is no specific pharmaceutical treatment currently available that can reverse the course of this disease. Notably, mesenchymal stem cells (MSCs) show great promise for the management of AKI by targeting multiple pathophysiological pathways to facilitate tubular epithelial cell repair. It has been well established that the unique characteristics of MSCs make them ideal vectors for gene therapy. Thus, genetic modification has been attempted to achieve improved therapeutic outcomes in the management of AKI by overexpressing trophic cytokines or facilitating MSC delivery to renal tissues. The present article provides a comprehensive review of genetic modification strategies targeted at optimizing the therapeutic potential of MSCs in AKI.